Penyelesaian Surat Pertanggungjawaban Pada Kegiatan Bantuan Fasilitasi Kegiatan Keagamaan: (Studi Evaluasi Sebelum dan Setelah Sistem Voucher Di Bagian Kesejahteraan Rakyat Setda Kabupaten Karanganyar) - Ettik Sulastri; Yitno Puguh Martomo; Rochmulyani Rochmulyani; Timotius Suryadi; Samsi Samsi (Lembaga Pengembangan Kinerja Dosen, 2024)
This study evaluates the preparation of Accountability Letters (SPJ) for Religious Activity Facilitation Assistance in the Sub-Division of Spiritual Mental Development, Public Welfare Section, Regional Secretariat of Karanganyar Regency before and after the implementation of the voucher system. The voucher system is designed to improve accountability, efficiency, and timeliness in the management of aid funds. The results of the study indicate that the voucher system accelerates the completion of SPJ compared to the cash method, although there are still obstacles such as the workload of employees who hold concurrent positions and the need for complicated supporting documents. It is recommended to optimize the division of tasks and simplify administration to improve the effectiveness of SPJ management.